2008
DOI: 10.1088/0953-8984/20/04/045214
|View full text |Cite
|
Sign up to set email alerts
|

Search for ferromagnetism in SnO2doped with transition metals (V, Mn, Fe, and Co)

Abstract: Based on first-principles calculations, we have investigated electronic structures and magnetic properties of SnO 2 doped with V, Mn, Fe, and Co. Our results show that ferromagnetism is the ground state and that the Curie temperatures are expected to have high values for Fe-and Co-doped SnO 2 , which is in good agreement with the experimental observations (Ogale et al 2003 Phys. Rev. Lett. 91 077205; Coey et al 2004 Appl. Phys. Lett. 84 1332). However, in V-and Mn-doped SnO 2 , paramagnetism is more stable tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
61
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 37 publications
10
61
0
Order By: Relevance
“…This value is comparable to that reported by Ogale et al [5] for 5% Co-doped SnO 2 thin film. Such a high M si value can be explained in terms of unquenched d-orbital of the doped Co-ion and due to oxygen vacancy as explained in [40].…”
Section: Resultsmentioning
confidence: 97%
“…This value is comparable to that reported by Ogale et al [5] for 5% Co-doped SnO 2 thin film. Such a high M si value can be explained in terms of unquenched d-orbital of the doped Co-ion and due to oxygen vacancy as explained in [40].…”
Section: Resultsmentioning
confidence: 97%
“…The SnO 2 powder was milled by the planetary ball mill (Fritch Pulverisette-7, Germany) with WC vials. The inner diameter and volume of each vial were 40 mm and 45 cm 3 , respectively, and the WC balls with 15 mm diameter were used as the grinding media. About 2 g of SnO 2 powder was the starting material.…”
Section: Sample Preparation and Experimentalmentioning
confidence: 99%
“…The ab initio calculations for the (TM) x Sn 1-x O 2 (TM= V, Mn, Fe and Co) were performed [1][2][3], and it was concluded that ferromagnetic moments appeared for Fe, Co, but not for V and Mn. In the study by our group [4], the TM oxides (V 2 O 5 , VO 2 Except for the TM-doped SnO 2 , the room temperature ferromagnetism, induced by the oxygen vacancies, has been reported for SnO 2 thin films, nano-particles and nano-wires [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, they have Curie temperatures below 100 K making them unattractive for practical applications in future devices characterized by simultaneous control of spin and charge of electrons [1]. Recently, oxide (ZnO, TiO 2 , SnO 2 , In 2 O 3 )-based DMS materials have attracted considerable attention due to the reports of ferromagnetism at room temperature which open the possibility of their application in emerging field of thin-film magneto-optic and spin-electronic devices [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%